Body on the bayou - Byron, Ellen (Byron, Ellen. Cajun country mystery., 2016)
"Just days before a big wedding at the Crozat Plantation B & B, the bride's cousin is found murdered, and Maggie Crozat has another murder to unravel"--Book jacket flap.